2014
DOI: 10.1089/ars.2012.5091
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Mediates Acute Liver Injury in Irradiated Mice Lacking Sirtuin 3

Abstract: Aims: This study determined whether acute radiation-induced liver injury seen in Sirtuin3-/ -mice after exposure to Cs-137 c-rays was mediated by superoxide anion (O 2 -). Results: Male wild-type (WT) and SIRT3-/ -mice were given 2 · 2 Gy whole-body radiation doses separated by 24 h and livers were harvested 20 h after the second dose. Ex vivo measurements in fresh frozen liver sections demonstrated 50% increases in dihydroethidium oxidation from SIRT3 -/ -animals, relative to WT animals, before irradiation, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…FoxOs also engage in crosstalk with the sirtuin family proteins. For example, sirtuin 3 (SIRT3), a protein deacetylase, is an important regulator of mitochondrial oxidative metabolism after exposure to radiation and other oxidative stresses both in vitro and in vivo (146). It abrogates mitochondrial • O 2 − production by regulating SOD2 expression transcriptionally through FoxO3a as well as via deacetylation of SOD2 at lysine residues, which results in increased SOD2 activity (146).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…FoxOs also engage in crosstalk with the sirtuin family proteins. For example, sirtuin 3 (SIRT3), a protein deacetylase, is an important regulator of mitochondrial oxidative metabolism after exposure to radiation and other oxidative stresses both in vitro and in vivo (146). It abrogates mitochondrial • O 2 − production by regulating SOD2 expression transcriptionally through FoxO3a as well as via deacetylation of SOD2 at lysine residues, which results in increased SOD2 activity (146).…”
Section: Discussionmentioning
confidence: 99%
“…For example, sirtuin 3 (SIRT3), a protein deacetylase, is an important regulator of mitochondrial oxidative metabolism after exposure to radiation and other oxidative stresses both in vitro and in vivo (146). It abrogates mitochondrial • O 2 − production by regulating SOD2 expression transcriptionally through FoxO3a as well as via deacetylation of SOD2 at lysine residues, which results in increased SOD2 activity (146). These events also appear to crosstalk with p53 signaling insofar as SIRT3 may further promote cell survival after irradiation/oxidative stress by deacetylating the pool of p53 that translocates to the mitochondria in response to increased • O 2 − generation, thereby enhancing p53 degradation (146).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the IR conditions, the excessive generation of O 2 •− molecules caused mitochondrial dysfunction that contributes to liver injury [40]. Our study showed that the correlation between depletion of SOD activities and enhancement of apoptosis signals was due to radiation (Fig.…”
Section: Discussionmentioning
confidence: 66%